Autonomic breathing abnormalities in Rett syndrome: Caregiver perspectives in an international database study - MacKay, J.; Downs, Jennepher; Wong, K.; Heyworth, J.; Epstein, A.; Leonard, H. (BioMed Central Ltd, 2017)
© 2017 The Author(s). Background: Rett syndrome is a severe neurodevelopmental disorder associated with mutations in the MECP2 gene. Irregular breathing patterns and abdominal bloating are prominent but poorly understood features. Our aims were to characterize the abnormal breathing patterns and abdominal bloating, investigate the distribution of these by age and mutation type and examine their impact and management from a caregiver perspective. Methods: We invited previously recruited families from the International Rett Syndrome Study to complete a web-based questionnaire concer ning their family member with Rett syndrome aged between 2 and 57 years. We used logistic regression to investigate presence, frequency and impact of breath-holding, hyperventilation, or abdominal bloating by age group and mutation type. Age of onset for both breathing abnormalities was investigated using time-to-onset analysis, and the Kaplan-Meier method was used to estimate the failure function for the study sample. Descriptive statistics were used to characterize the management of irregular breathing. Results: Questionnaires were returned by 413/482 (85.7%) families. Breath-holding was reported for 68.8%, hyperventilation for 46.4% and abdominal bloating for 42.4%. Hyperventilation was more prevalent and frequent in those younger than 7 years of age and abdominal bloating in those aged over 20 years. Onset of breathing irregularities usually occurred during early childhood. Caregivers perceived that daily life was considerably impacted for almost half (44.1%) of those with abdominal bloating and in just over than a third of those with breath-holding (35.8%) or hyperventilation (35.1%). Although perceived impact was broadly comparable between age and mutation groups for breath-holding, hyperventilation and abdominal bloating, girls and women with a p.Arg294âˆ—mutation were considered to be more affected by all three conditions. Only 31 individuals had received medically prescribed treatments including 12 different medications, added oxygen, rebreathing apparatus or non-invasive ventilation. Conclusions: Autonomic disturbances are prevalent and burdensome in Rett syndrome. This information may guide the design of inclusion criteria and outcome measures for clinical intervention trials targeting autonomic abnormalities. Further investigation of available treatments is necessary to delineate evidence-based management pathways.